LIGNIN REMOVAL FROM CORNCOB BY MICROWAVE-COUPLED PEROXIDE TREAT-MENT - Mladenović, Dragana (Journal on Processing and Energy in Agriculture, 2024)
Lignocellulosic biomass comprises the crop residues, which remain in large quantities from various stages of crop processing. Its main constituents, cellulose, hemicellulose, and lignin, are interlinked by hydrogen and covalent bonds and form a robust and intricate matrix making it resistant to enzymatic degradation. Pretreatment is crucial in lignocellulosic biomass processing, aiming to remove lignin and enhance enzyme access to polysaccharides. This study examines how microwave-assisted peroxide pretreatment affects the delignification of corncobs, aiming to enhance the efficiency of utilizing this agricultural residue in fermentation processes. Taguchi orthogonal array was used to optimize pretreatment conditions and assess the effects of individual parameters (temperature, H2O2 dose, and pretreatment time) on delignification efficiency. The results showed the significant influence of pretreatment conditions on lignin removal from corncobs, with the highest delignification achieved at an H2O2 dose of 500 mg/g, temperature of 100 °C, and pretreatment time of 2 minutes. H2O2 dose had the most substantial impact on the delignification, followed by temperature and pretreatment time. The observed 81.6% delignification and 61.9% increase in cellulose content are pivotal for enzymatic hydrolysis efficiency. This improvement suggests enhanced enzyme availability during hydrolysis and reversible binding to polysaccharide active sites, potentially leading to higher sugar yields.